Analysis of classification and surgical treatment of cervical dumbbell-shaped tumors - Jia-gang LIU; Hai-feng CHEN; Yu HU; Si-qing HUANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Objective To investigate the clinical characteristics, classification, surgical approach, complication and prognosis of cervical dumbbell-shaped tumors.  Methods Twenty-six consecutive cases with cervical dumbbell-shaped tumors were retrospectively studied. According to tumor location by imaging examination, all tumors were divided into 3 types. Type Ⅰ (17 cases) was mostly intravertebral and foraminal. Surgery through posterior approach was performed and internal fixation was operated in 8 cases. Type Ⅱ (4 cases) was mostly paravertebral and foraminal. Surgery through the anterolateral approach was performed without internal fixation. Type Ⅲ (5 cases) was equalization of intravertebral and paravertebral, and underwent surgery through combined posterior-anterolateral approach and internal fixation was performed in all of those cases. If the unilateral facet joint was destroyed, internal fixation was necessary. Lateral mass screw internal fixation and transpedicular screw fixation supplemented by fusion with autologous iliac bone graft were used to maintain cervical spinal stability.  Results Among 26 patients there were 19 schwannomas, 4 neurofibromas, 2 gangliocytoma and 1 spinal meningioma. Total and subtotal tumor resection was achieved in 23 and 3 patients respectively. Among them 50% (13/26) of the cases were used internal fixation including 8 TypeⅠand 5 Type Ⅲ patients. The follow-up period was from 7 to 62 months, and mean time was 30 months. Four cases (15.38%) were found local tumor recurrence. Two cases suffered with surgical infection and cerebrospinal fluid leakage. There was no spinal cord injury and spinal deformity.  Conclusion In order to increase the total resection rate and decrease recurrence rate, surgical approach should be selected according to the imaging classification of tumors. Stability reconstruction is absolutely necessary for the patients with facet joint destroyed. doi: 10.3969/j.issn.1672-6731.2013.11.006 Video: http://www.cjcnn.org/index.php/cjcnn/pages/view/v13n11a6